Association between serum hepcidin-25 and primary resistance to erythropoiesis-stimulating agents in chronic kidney disease: a secondary analysis of the HERO trial - Gummer, J.; Trengove, R.; Pascoe, E.; Badve, S.; Cass, A.; Clarke, P.; McDonald, S.; Morrish, A.; Pedagogos, E.; Perkovic, V.; Reidlinger, D.; Scaria, A.; et al. (Wiley-Blackwell, 2017)
Background: Pentoxifylline has been shown to increase haemoglobin levels in patients with chronic kidney disease (CKD) and erythropoietin-stimulating agent (ESA)-hyporesponsive anaemia in the Handling Erythropoietin Resistance with Oxpentifylline multicentre double-blind, randomized controlled trial. The present sub-study evaluated the effects of pentoxifylline on the iron-regulatory hormone hepcidin in patients with ESA-hyporesponsive CKD. Methods: This sub-study included 13 patients in the pentoxifylline arm (400 mg daily) and 13 in the matched placebo arm. Hepcidin-25 was measured by ultra performance liquid chromatography/quadrupole time-of-flight mass spectrometry following isolation from patient serum. Serum hepcidin-25, serum iron biomarkers, haemoglobin and ESA dosage were compared within and between the two groups. Results: Hepcidin-25 concentration at 4 months adjusted for baseline did not differ significantly in pentoxifylline versus placebo treated patients (adjusted mean difference (MD) -7.9 nmol, P = 0.114), although the difference between the groups mean translated into a > 25% reduction of circulating hepcidin-25 due to pentoxifylline compared with the placebo baseline. In paired analysis, serum hepcidin-25 levels were significantly decreased at 4 months compared with baseline in the pentoxifylline group (-5.47 ± 2.27 nmol/l, P < 0.05) but not in the placebo group (2.82 ± 4.29 nmol/l, P = 0.24). Pentoxifylline did not significantly alter serum ferritin (MD 55.4 mcg/l), transferrin saturation (MD 4.04%), the dosage of ESA (MD -9.93 U/kg per week) or haemoglobin concentration (MD 5.75 g/l). Conclusion: The reduction of circulating hepcidin-25 due to pentoxifylline did not reach statistical significance; however, the magnitude of the difference suggests that pentoxifylline may be a clinically and biologically meaningful modulator of hepcidin-25 in dialysis of patients with ESA-hyporesponsive anaemia. © 2016 Asian Pacific Society of Nephrology.